English English - Listiana, Amalia; Disman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
Economic literacy and interest in entrepreneurship are two important aspects that can help elementary school students face economic challenges in the future. Someone who is skilled in economics is able to make wise decisions regarding their finances, while entrepreneurship can help create many jobs and grow the economy. The aim of this research is to examine the influence of economic literacy on elementary school students' interest in entrepreneurship in the city of Bandung by applying the Project Based Learning method. Simple regression approach used in this study while data collected by questionnaire. The population in this research is elementary school students in Bandung City. The sampling technique used a purposive sampling approach, so the total sample was 96, namely elementary school students in Bandung City. The analytical tool used is simple linear regression analysis. The research results show that economic literacy has a significant effect on increasing the entrepreneurial interest of elementary school students in Bandung City using the Project Based Learning (PJBL) learning model. With model capability of 43.2%, while the remaining 56.8%, the entrepreneurial interest of elementary school students in Bandung City using the Project Based Learning (PJBL) learning model is influenced by other factors not examined in this research.